2007
DOI: 10.1038/sj.gt.3302999
|View full text |Cite
|
Sign up to set email alerts
|

Non-viral delivery of interleukin-2 and soluble Flk-1 inhibits metastatic and primary tumor growth in renal cell carcinoma

Abstract: Treatments for renal cell carcinoma, while promising, are still limited by toxicity and cost. In the hopes of finding a novel compound or combination, we developed a plasmid containing the genes for interleukin-2 (IL-2) and soluble vascular endothelial growth factor receptor 2 (msFlk1). The plasmid, p2CMVIL2/msFlk1, demonstrated similar in vitro transgene expression of IL-2 or msFlk1 compared to their single-agent counterparts. Subcutaneous tumor growth was significantly inhibited in the p2CMVIL2/msFlk1 group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In many studies, Renca cells are injected s.c. to produce localized tumors or intravenously (i.v.) to produce experimental lung metastases [29], [30], [31], [32], [33]. We had previously shown that intratumoral administration of Ad5mTRAIL plus CpG1826 could lead to the eradication of localized s.c. Renca tumors in mice [16].…”
Section: Resultsmentioning
confidence: 99%
“…In many studies, Renca cells are injected s.c. to produce localized tumors or intravenously (i.v.) to produce experimental lung metastases [29], [30], [31], [32], [33]. We had previously shown that intratumoral administration of Ad5mTRAIL plus CpG1826 could lead to the eradication of localized s.c. Renca tumors in mice [16].…”
Section: Resultsmentioning
confidence: 99%
“…Many investigators believe that PEI‐based DNA transfer systems are well suited for use in gene therapy for the treatment of cancer. ( 3,31–34 ) Although PEI has been proven to be effective in gene delivery due to its condensation of DNA, it is not biodegradable. Moreover, the improvement of transfection efficiency is accompanied by increased cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this polymer has been used to deliver genes to several different cancers, myocardium and corpus cavernosum. [45][46][47][48][49] In summary, we have demonstrated that ischemiainducible VEGF gene therapy improves the efficacy of VEGF gene therapy for myocardial infarction through decreased apoptosis and increased angiogenesis.…”
Section: Ischemia-inducible Gene Therapy Jw Yockman Et Almentioning
confidence: 89%